Exploring Ichthyofaunal Diversity and Water Quality in the Bhadar-II Reservoir, Gujarat, India - Tandel, Janshi; Chavda, Vanraj; Sakariya, Kishan; Rana, Rushirajsinh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The study was conducted to assess the fish diversity and water quality in the Bhadar-II reservoir, located in Rajkot district of Gujarat. Monthly sampling was carried out from September 2023 to April 2024. A total of 19 fish species were recorded during the study period. Cypriniformes was the dominant order in terms of species diversity (9 species), followed by Siluriformes (5 species), Anabantiformes (3 species), Osteoglossiformes (1 species) and Cichliformes (1 species). The dominant families were Cyprinidae (9 species), followed by Channidae (3 species), Siluridae (2 species), and 1 species each from Claridae, Heteropneustidae, Cichlidae, Pangasiidae, and Notopteridae. The catfish population was the most prevalent, accounting for 26% of the total fish population, followed by minor carp at 21%. Major carp, exotic fish, and murrels each contributed 16%, while featherback fish had the lowest at 5%. The fish data was subjected to species diversity analysis. The Shannon-Wiener Index values ranged from 1.776 to 2.546, indicating monthly fluctuations in diversity levels. This range suggests that the habitat structure was moderately stable. Pielou's Evenness Index values ranged from 0.8080 to 0.8880, showing a gradual increase in evenness over time. This increase can be attributed to a decline in the population of the dominant species. Species richness, as measured by the Margalef Richness Index, ranged from 1.278 to 2.477, with the highest species richness observed in November during the winter season. Monthly observations of physicochemical parameters showed the range of water temperature from 23.4°C to 30.1°C, dissolved oxygen levels from 6.7 to 8.9 mg/l, pH from 7.6 to 8.3, alkalinity between 139.4 to 156.2 mg/l, and total hardness from 94.2 to 133.1 mg/l.